Bimbingan Belajar Untuk Meningkatkan Kemampuan Membaca, Menulis, Berhitung, dan Berbahasa Asing Pada Anak-Anak di Desa Pulau Telo Baru - Allisa Munawarrah; Hartati Agustin; Ikrimatul Ulya; Muhammad Al Fisah; Riannur Riannur; Muhammad Jailani Alkadri; Muhammad Rafi’I; Norhaliza Norhaliza; Pepita Sari; Rabiatul Adawiyah; Riska Tri Listiani (Jurnal Informasi Pengabdian Masyarakat, 2023)
This service aims to improve children's reading, writing, arithmetic and foreign language skills in the village of Telo Baru Island through providing tutoring. Apart from that, this research tries to compare students' interest in learning at school with tutoring at KKN posts, as well as identifying students' motivation to study outside of school. SWOT analysis is used as a research method with a focus on strengths, weaknesses, opportunities and threats. The research results show that student strengths can be an indicator of understanding material at school. Student weaknesses related to lack of understanding of basic material need to be addressed. Opportunities arise in understanding the causes of student failure and learning difficulties. Corrective action involves efforts to increase interest in learning through a comfortable atmosphere at school and family support. In conclusion, this service focuses on understanding and overcoming barriers to student learning, as well as taking advantage of opportunities to improve the quality of education in the village of Telo Baru Island.